2009
DOI: 10.1002/j.0022-0337.2009.73.11.tb04823.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gender on Performance of Undergraduate Dental Students at the University of Jordan, Amman

Abstract: The purpose of this study was to see if gender-based differences exist in the performance of dental students at the University of Jordan (UJ), Amman. The retrospective analysis included data from two groups of students: 413 fourth-year dental students (178 males and 275 females) from four consecutive years (2005 through 2008) and 357 fifth-year students (128 males and 229 females) who graduated in the years 2005 to 2008. The influence of gender on the results of the fourth-year students in six theoretical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 15 publications
4
20
3
Order By: Relevance
“…Students who are entering the medical field already have concerns about medical school in the process of anticipating the necessary adjustment to the challenges ahead of them. Preventive programs should begin early in the medical education to address the wide variety of concerns which are related to academic program and interpersonal relationships (Smith et al,2007).…”
Section: Anxiety and Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Students who are entering the medical field already have concerns about medical school in the process of anticipating the necessary adjustment to the challenges ahead of them. Preventive programs should begin early in the medical education to address the wide variety of concerns which are related to academic program and interpersonal relationships (Smith et al,2007).…”
Section: Anxiety and Stressmentioning
confidence: 99%
“…However they reported that the English language skills was the significant predictor of academic performance rather than gender. Since the proportion of female medical students is increasing in medical schools with time, there is concern regarding their differing performance in examinations (Sawair et al, 2009;Hinkley,1997;Hall et al, 2001). Since the medium of communication in the medical schools is English, the Arabic speaking students find English as a challenge in learning the medical subjects.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to gender, research indicates that women performed better than men in certain settings, while men performed better than women in other settings [4][5][6]. Female medical students demonstrated a better performance than male medical students in clinically based performance examination [6][7][8][9]. Results of different studies indicated that men were better than women on several standardized written examinations as well as in certain intelligence test assessment [01-01].…”
Section: Introductionmentioning
confidence: 99%
“…The proportions of female students in medical schools is increasing with time however, concerns remain about differing performance in examinations [6,02,03]. In Saudi Arabia, the number of female students in tertiary education in the kingdom rose six-fold between 1970 and 2007 compared with a quadrupling of male enrolments during the same period [04].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, male students had significantly less correct answers compared to female students regarding cause and diagnosis of barodontalgia (Fig 1). Some studies have discussed the possible reasons why Jordanian female students might outperform male dental students (Sawair, Baqain et al 2009), which might also be applicable to Saudi students. These factors include that acceptance grades to enroll in dental schools is very competitive among females, as more females might prefer dentistry as a profession.…”
Section: Discussionmentioning
confidence: 99%